First Line Treatment of Meniere’s Disease: A Randomized Controlled Trial - Acharya, Anup; Singh, Madan Mohan; Shrestha, Arati (Journal of Lumbini Medical College, 2017)
Introduction: There is no consensus on the first line medical treatment of Meniere disease to produce symptomatic improvement and slow the disease progress. Dietary salt restriction, diuretics, and vasodilators like betahistine are among the first line drugs that have been used for long. There is lack of evidence due to paucity of quality studies to support their effectiveness and advocate their use. This study is done to evaluate the effectiveness of three first line treatment of Meniere disease i.e. salt restriction, oral diuretics, and betahistine. Methods: Double blind randomized controlled trial was carried out in out-patient clinic of Ear Nose and Throat department of Lumbini Medical College Teaching Hospital. Cases were randomized into three groups; dietary salt restriction, diuretics as amiloride and furosemide, and vasodilator as betahistine. Pre and post treatment evaluation was done in terms of number and severity of vertigo, tinnitus, and hearing outcome. Results: There were a total of 97 cases with F:M ratio of 1.1:1. Mean age of patients was 47.86 yr (SD=12.7). Twenty-nine (30%) were treated with dietary sodium restriction alone (Group A), 35 (36%) were treated with diuretics (Group B) and the rest 33 (34%) were treated with vasodilator (betahistine, Group C). There was no significant difference in hearing outcome in any group. Tinnitus was significantly improved in Group B. Number of vertigo attack was significantly decreased in Group B and Group C. Severity of vertigo was significantly decreased in Group B. Conclusion: Dietary salt restriction alone was not effective in controlling any aspect of the disease whereas diuretics were effective in reducing tinnitus and number and severity of vertigo. Betahistine was effective in reducing the number of vertigo attacks but not effective on other aspects of the disease. J. Lumbini. Med. Coll.Vol 4, No 2, July-Dec 2016, page: 68-71 DOI: https://doi.org/10.22502/jlmc.v4i2.93